An Overview on Gastroretentive Drug Delivery System: Current Approaches and Advancements - Anu Tomar; Aakash Upadhyay; S K Gupta; Shobhit Kumar (Current Research in Pharmaceutical Sciences, 2019)
Gastroretentive Drug Delivery System (GRDDS) can elevate the controlled delivery of drugs that have an absorption window by continuously releasing the drug for a constant period of time before it extends its absorption site. This includes floating system, dilation and expanding system, muco - adhesive system, high density system and other postponed gastric emptying devices. The present article briefly about the formulation consideration for GRDDS, factors controlling gastric retention time, advantages, disadvantages and evaluation of GRDDS.